(untitled) (Journal of Laboratory Animal Science, 2022)
The objective of this study was to determine the prevalence of Encephalitozoon cuniculi infection through serologic and histopathologic examination of laboratory rabbits from suppliers in India. One hundred and thirty-one New Zealand White rabbits procured from two different Indian suppliers were used for this study. All rabbits were clinically normal at receipt and during the period of experiment. Serological examination was carried out for the detection of E. cuniculi antibodies using ELISA tests. The select tissues were collected and processed for light microscopic evaluation. Among 131 rabbits evaluated 43 (33%) were seropositive for E. cuniculi. The microscopic changes in the brain and spinal cord (granulomatous inflammation and/or perivascular infiltrates) and kidneys (interstitial nephritis) were consistent with E. cuniculi infection. A good correlation (84%) between serological and microscopic findings was observed. Other background microscopic findings were minimal and consistent with hepatic (3%) and intestinal (5%) Eimeriasis (Coccidiosis). The microscopic changes consistent with otitis externa and otitis media, possibly related to external parasitic infection were observed in a few (11%) rabbits. Based on these findings, it is recommended that, rabbits should be serologically screened for E. cuniculi at supplier’s breeding colony to remove carriers. Furthermore, before supplying rabbits to research facility, serology should be performed by the supplier to exclude seropositive animals. In addition, the research facilities also should consider performing serological testing to ensure that only seronegative animals are selected for experiments. This will minimize the variability in test results, avoid spurious observations and aid in scientific data interpretation